2022
DOI: 10.7554/elife.79762
|View full text |Cite
|
Sign up to set email alerts
|

Canonical Wnt signaling and the regulation of divergent mesenchymal Fgf8 expression in axolotl limb development and regeneration

Abstract: The expression of Fibroblast growth factors (Fgf) ligands in a specialized epithelial compartment, the Apical Ectodermal Ridge (AER), is a conserved feature of limb development across vertebrate species. In vertebrates, Fgf 4, 8, 9, and 17 are all expressed in the AER. An exception to this paradigm is the salamander (axolotl) developing and regenerating limb, where key Fgf ligands are expressed in the mesenchyme. The mesenchymal expression of Amex.Fgf8 in axolotl has been suggested to be critical for regenerat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 67 publications
6
19
0
Order By: Relevance
“…Then, we surveyed the established AER markers to determine the transcriptional similarities of these axolotl cells with the AER in other species ( Figures 1E and S5 ). The large majority of axolotl cells in this cluster co-expressed many of the AER markers 1 , such as Wnt5a and Msx2 , whilst some others (e.g., Fgf8 ) were absent (Figures 1E and S5) , in alignment with recent reports 4, 7 . A further transcriptome-wide comparison found not only a high similarity of AER-like axolotl cells to the AER cells in other species, but also that this population was distinct from non-AER basal ectodermal cells (Figures 1F and S6) .…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…Then, we surveyed the established AER markers to determine the transcriptional similarities of these axolotl cells with the AER in other species ( Figures 1E and S5 ). The large majority of axolotl cells in this cluster co-expressed many of the AER markers 1 , such as Wnt5a and Msx2 , whilst some others (e.g., Fgf8 ) were absent (Figures 1E and S5) , in alignment with recent reports 4, 7 . A further transcriptome-wide comparison found not only a high similarity of AER-like axolotl cells to the AER cells in other species, but also that this population was distinct from non-AER basal ectodermal cells (Figures 1F and S6) .…”
Section: Introductionsupporting
confidence: 90%
“…Axolotl AER cells had comparable signaling potential to the AER in other species (Figures 1G and S7) . Meanwhile, individual pathway examination revealed the axolotl AER differs in paralog and co-factor expressions, particularly in the FGF and WNT pathways (Figure S8) , complementing and extending previous observations 4, 7, 21 . We could not detect noticeable differences in transcriptional levels associated with DELTAs, BMPs, or TGFbs (Figure S8) .…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…It would be interesting to investigate whether RXR-RAR heterodimers play a role in tail regeneration in TRDKO. In addition, Wnt and FGF pathways are well-known signaling pathways implicated in tail and limb regeneration [ 26 , 72 , 73 ]. We found that wnt3a , wnt5a , fgf10 and fgf8 were expressed at much higher levels in the patterning and outgrowth period in the TRDKO tail compared to wild type tail after amputation at stage 61.…”
Section: Discussionmentioning
confidence: 99%